Methylprednisolone Plasma Concentrations During Cardiac Surgery With Cardiopulmonary Bypass in Pediatric Patients - van Saet, Annewil; Zeilmaker-Roest, Gerdien A.; Veen, Kevin M.; de Wildt, Saskia N.; Sorgel, Fritz; Stolker, Robert J.; Bogers, Ad J. J. C.; Tibboel, Dick (Frontiers in Cardiovascular Medicine, 2021)
Abstract Introduction To our knowledge MP PK and plasma concentrations have not been comprehensively investigated in children with congenital heart disease undergoing cardiac surgery with CPB. It is unknown whether there is a significant influence of CPB on the plasma concentrations of MP, and whether this may be an explanation for the limited reported efficacy of steroid administration in cardiac surgery with CPB. Methods The study was registered in the Dutch Trial Register (NTR3579; https://www.trialregister.nl/trial/3428). MP 30 mg/kg was administered as an intravenous bolus after induction of anesthesia. MP plasma concentration was measured with LC MS/MS and analyzed using mixed-effects modeling. Results 39 patients were included in the study, of which 3 were excluded. There was an acute decrease in observed MP plasma concentration on initiation of CPB (median 26.8 %, range 13.9 %-48.14 %, p < 0.001). We found a lower intercept (p = 0.02), as well as a less steep slope of the model predicted MP plasma concentration versus time curve for neonates (p = 0.048). A lower intercept (p 0.01), as well as a less steep slope (p 0.0024) if the volume of cellsaver blood processed was larger than 91 ml/kg was also found. Discussion We report similar MP plasma concentrations as in earlier studies performed in children undergoing CPB, and we confirmed the large interindividual variability in achieved MP plasma concentration with weight-based MP administration. A larger Vd and a lower Cl of MP for neonates were suggested. The half-life of MP in our study was calculated to be longer than 6 hours for neonates, 4.7 hours for infants, 3.6 hours for preschool children and 4.7 hours for school children. The possible influence of treatment of PHT with sildenafil and temperature needs to be investigated further.